INDEKS STOMATA, PANJANG AKAR DAN TINGGI TANAMAN SEBAGAI INDIKATOR KEKURANGAN AIR PADA TANAMAN PADI VARIETAS IR64 DAN CIHERANG - Angga Rahabistara Sumadji; Karlina Purbasari (Universitas Merdeka Madiun, 2018)
Rice plant is very important staple food and has been the main staple food for half of people in the world. Rice is the main commodity and food support in Indonesia. Many efforts to increase rice productivity face some obstacles, such as environmental factor and place. Water supply becomes the main problem in rice planting. Rice plant needs different volume of water for each phase of growing. The research goal is to find the effect of lacking water towards the stomata index, the length of root, and the height of the rice plant of IR64 variety and Ciherang variety. The result of the research concludes that IR64 variety has lower stomata index than Ciherang variety does. IR64 variety has low stomata index because IR64 variety belongs to indica variety that has low transpiration so that it can be planted in dry area. The length of root of IR64 variety is longer than Ciherang variety which supports the variety to be planted in dry area. IR64 variety is 83-88 cm lower than Ciherang variety.Keywords—: stomata index, length of root, height of the plant, rice variety